Novel Technique For Selective Harmonic Elimination Pulse-With Modulation Control For Voltage Source Inverters Using Hybrid Real-Coded Genetic Algorithm - Dahidah, Mohamed S.A. (2007)
This dissertation proposes an effiient optimisation technique called the hybrid eal-coded genetic algorithm (HRCGA) that reduces significantly the computational burden of obtaining the solution of the nonlinear equation system resulting in fast convergence.